2012
DOI: 10.1159/000337172
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Cocaine Exposure Decreases Parvalbumin-Immunoreactive Neurons and GABA-to-Projection Neuron Ratio in the Medial Prefrontal Cortex

Abstract: Cocaine abuse during pregnancy produces harmful effects not only on the mother but also on the unborn child. The neurotransmitters dopamine and serotonin are known as the principal targets of the action of cocaine in the fetal and postnatal brain. However, recent evidence suggests that cocaine can impair cerebral cortical GABA neuron development and function. We sought to analyze the effects of prenatal cocaine exposure on the number and distribution of GABA and projection neurons (inhibitory interneurons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…Preclinical research has demonstrated significant effects of PCE on brain regions involved in emotional regulation, motivational control, and addiction vulnerability during adolescence (Chambers and Potenza, 2003)-eg, anterior cingulate (ACC) (Harvey, 2004), prefrontal cortex (PFC) (McCarthy and Bhide, 2012), and ventral striatum (VS) (Harvey et al, 2001;Wang et al, 2013). In humans, neurostructural (Rando et al, 2013) and neurofunctional (Li et al, 2009;Sheinkopf et al, 2009;Li et al, 2011) alterations (eg, during response inhibition, resting state alterations) in regions of the VS and PFC have also been reported among adolescents with PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical research has demonstrated significant effects of PCE on brain regions involved in emotional regulation, motivational control, and addiction vulnerability during adolescence (Chambers and Potenza, 2003)-eg, anterior cingulate (ACC) (Harvey, 2004), prefrontal cortex (PFC) (McCarthy and Bhide, 2012), and ventral striatum (VS) (Harvey et al, 2001;Wang et al, 2013). In humans, neurostructural (Rando et al, 2013) and neurofunctional (Li et al, 2009;Sheinkopf et al, 2009;Li et al, 2011) alterations (eg, during response inhibition, resting state alterations) in regions of the VS and PFC have also been reported among adolescents with PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal phencyclidine (PCP) exposure reduces the density of PV-expressing cINs and disrupts the formation of prefrontal cortical circuits leading to behavioral deficits in mice 142 . Intriguingly, prenatal cocaine exposure, which is thought to primarily target dopaminergic and serotonergic systems, impairs tangential migration and causes a reduction of both the total number of cINs and the percentage of PV-expressing cINs in the medial prefrontal cortex of adult mice 143,144 . The epidemiological significance of in utero methamphetamine, PCP, and cocaine exposures, however, is unknown.…”
Section: Disruption Of Cortical Interneuron Developmentmentioning
confidence: 99%
“…Previous preclinical and clinical studies have implicated PCE in impacting corticolimbic brain regions including the anterior cingulate (ACC) (Harvey, 2004), prefrontal cortex (PFC) (Grewen et al, 2014; McCarthy and Bhide, 2012; McCarthy et al, 2014), amygdala (Li et al, 2016) and ventral striatum (Harvey et al; Wang et al, 2013). Dysregulation of corticolimbic pathways have been shown in response to reward-related and stressful cues among individuals with obesity and with cocaine addiction (Jasinska et al, 2014; Jastreboff et al, 2013; Potenza, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike some other functional connectivity analytic approaches, ICD is data-driven and does not require the definition of an arbitrary threshold or regions of interest and thus is model-free and unbiased. While ICD does not require hypotheses, given previous findings, we hypothesized that ICD would identify connectivity differences in corticolimbic (Harvey, 2004; McCarthy and Bhide, 2012; McCarthy et al, 2014) and DMN (Li et al, 2013; Li et al, 2011) regions during stressful and appetitive processing between the PCE and NDE groups, as well as reveal less well-characterized regions and networks. We also hypothesized that food-craving scores would be inversely correlated with the degree of connectivity in these regions during the stressful and appetitive conditions.…”
Section: Introductionmentioning
confidence: 99%